Comparative Study of Protective Effect of Tomato Juice and N-Hexane Extract of Tomato on Blood Lipids and Oxidative Stress in Cholesterol-Fed Rats - Islam, Nadia; Akhter, Nargis (Anwer Khan Modern Medical College Journal, 2017)
Background: Hyperlipidemia is a well-established risk factor in pathogenesis of atherosclerosis and atherosclerosisassociated conditions by enhancing oxidative stress. Dietary supplementation of tomato which is enriched with antioxidants especially like lycopene may therefore be effective in reducing oxidative stress during hyperlipidemic condition. The study evaluates and compares the protective effect of tomato juice and n-Hexane extract of tomato on oxidative stress in hyperlipidemic rats. Methodology: This experimental study was carried out among 42 rats divided in 7 groups. Rats were treated with 0.5% cholesterol (suspension of cholesterol powder in soybean oil) at a dose of 50 mg/ ml once daily through intragastric tube for 8 weeks. In other two groups of rats tomato juice (1 mg/kg) or n-Hexane extract of tomato (1 mg/kg) with 0.5% cholesterol were given orally once daily through intragastric tube for 8 weeks. Serum lipid profile, body weight, plasma malondialdehide (MDA) and erythrocyte reduced glutathione(GSH) levels were measured after 8 weeks in all the groups. Results: Administration of cholesterol caused significant increase (p<0.001) in serum cholesterol, serum triglyceride (TG), serum low-density lipoprotien cholesterol (LDL-C)and significant decrease (p<0.001) in serum high-density lipoprotein cholesterol (HDL-C) which were associated with significant increment (p<0.001) in plasma MDA levels and depletion(p<0.001) in erythrocyte GSH levels. Concomitant treatment of tomato juice or n-Hexane extract of tomato with cholesterol reduced (p<0.001) serum cholesterol, serum LDL-C, body weight and increased serum HDL-C level in cholesterol plus tomato juice treated group (p<0.001) and in cholesterol plus n-Hexane extract of tomato treated group (p<0.05).But serum triglyceride was decreased(p<.05) only in cholesterol plus tomato juice treated group. Simultaneous treatment of tomato juice or n-Hexane extract of tomato with cholesterol decreased (p<0.001) plasma MDA level and increased (p<0.001) erythrocyte GSH level. However, significant differences were noted between the effect of tomato juice and n-Hexane extract of tomato on serum cholesterol (p<0.001), serum triglyceride (p<.05), serum LDL-C (p<0.001), serum HDL-C level(p<0.01) and plasma MDA(p<0.001) and erythrocyte GSH (p<0.001) levels. But no significant difference was noted on body weight. Conclusion: It may be concluded that both tomato juice and n-Hexane extract of tomato offered protection against hyperlipidemia and oxidative stress, but the protection afforded by tomato juice was superior to n-Hexane extract of tomato. Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 30-37